0038 A national scan of campus sexual violence prevention efforts. (26th April 2015) - Le, David
Abstract : Statement of purpose: The California Coalition Against Sexual Assault's national project PreventConnect conducts a scan each year of trends in prevention to inform its activities to support sexual and domestic violence prevention efforts. With the establishment of the White House Task Force to Protect Students from Sexual Assault in January 2014 and subsequent release of its first report in April 2014, 1 PreventConnect conducted a scan specific to prevention efforts on college campuses. Methods/Approach: The scan identifies trends in current sexual violence prevention efforts on campuses; mandates and regulations; challenges and opportunities in designing, implementing and evaluating sexual violence prevention strategies; and commonly used approaches. Given the dearth of research in peer-reviewed journals that demonstrate proven effective approaches to prevent sexual violence, this effort details contextual and experiential evidence based on the work of stakeholders. The scan represents a summary of CALCASA's experience working with college campuses as technical assistance provider to the national DOJ Campus Program since 1999, participating in the Department of Education's VAWA Negotiated Rulemaking Committee, and from key informant interviews Results: The scan provides a view of the current status of sexual violence prevention efforts and identifies opportunities and gaps based on CALCASA's 3-pronged approach to addressing and preventing sexual assault on college campuses which include: Survivor Centredness Community Collaboration and Engagement Comprehensive Prevention Comprehensive prevention includes strategies that address sexual violence before it happens (primary prevention) as well as address sexual violence after it takes place. Comprehensive prevention on college campuses requires more than just providing information at orientation for incoming students. It is also critical that Comprehensive Prevention efforts saturate the campus community. Conclusions: The scan provides important foundation of knowledge to inform strategies to lead to more effective policies, responses and procedures when a sexual assault occurs and can create a shift in cultural norms on campuses that can prevent sexual assault before it begins. Significance and contribution to the field: Given the national attention to sexual violence on college campuses, public health, violence and injury programs have an important contribution toward strengthening sexual violence prevention efforts. Understanding the current landscape of prevention efforts is essential to prevention practice.